Словарь народных географических терминов: словарь / Э. М. Мурзаев - Мурзаев Эдуард Макарович (Мысль, 1984)
Экземпляры: (20160305) / Инвентарный номер: 11678 / Сис.шифр: 81.2Рус-3 / Авт.знак: М 91 / ББК: 81.2Рус-3